À la trace - Cazajous-Augé, Claire (ENS Éditions, 2022)
For many years, the North American writer and environmental activist Rick Bass has noted the disappearance of many animal species and their habitats. How can we alert people to the alarming loss of biodiversity and encourage them to change their behavior and practices towards animals? How can we describe the richness and fragility of North American fauna without attracting the curious into spaces threatened by human presence? What role can fiction play in this activist enterprise? Through the study of Rick Bass’ short stories, this book examines how fictional writing plays an essential role in protecting the non-human world and celebrating the ways of being of animals. Adopting a multidisciplinary approach, it contributes to ethical, philosophical, and aesthetic debates on the relationship between literature and animals. One of the distinguishing features of Rick Bass’ poetry is the way in which it draws on the structure and substance of fictional writing to make us experience the infinite variety of non-human modes of existence. Playing with rhythmic devices, sounds, and syntax, Bass’ writing can evoke the elusive presence of a deer, the circular movements of swans, or the silent suffering of a wounded mule. Leading us towards other styles, other ways to phrase experience, it directs our own modes of existence towards more ethical behaviours. This book, the first French-language study on the work of Rick Bass, is more broadly aimed at those interested in the representation of animals in literature and the arts.